Preparation process of flame-retardant adhesive for copper-clad plate

By adding phosphorus-containing polyaryleether to the epoxy resin adhesive for copper clad plates to form a nitrogen-phosphorus flame retardant system, the problem of poor flame retardancy and toughness of epoxy resin adhesive is solved, and its flame retardant performance and toughness are significantly improved.

CN119529724AActive Publication Date: 2025-02-28HEILONGJIANG ZHIANSHENG NEW MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510106161.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-02-28
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The flame retardancy and toughness of epoxy resin adhesives for copper clad plates are poor, which affects its performance in copper clad plate applications.

Method used

By adding phosphorus-containing polyarylee to the epoxy resin adhesive, a nitrogen-phosphorus flame retardant system is formed using the DOPO group and phenylimide ring structure to enhance the flame retardant performance and toughness of the adhesive.

Benefits of technology

The flame retardant properties and toughness of epoxy resin adhesives are significantly improved, the peak heat release rate and total heat release amount are reduced, and the impact strength and bending strength of the adhesive are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, and discloses a preparation process of a flame-retardant adhesive for a copper-clad plate, and the flame-retardant adhesive for the copper-clad plate is obtained by mixing a solvent, epoxy resin, phosphorus-containing polyarylether, a defoaming agent, a curing agent and the like. A molecular main chain of the phosphorus-containing polyarylether contains a DOPO group and a phenyl imide ring structure, a nitrogen-phosphorus flame-retardant system is formed, a very good condensed phase flame-retardant effect is achieved, an expanded carbon layer is formed in an adhesive matrix during combustion, the phosphorus-containing polyarylether has an excellent flame-retardant effect, and the heat release rate peak value and the total heat release amount are remarkably reduced. The phosphorus-containing polyarylether contains a phenyl imide ring with large rigidity and high structural stability, and a side chain contains a flexible long-chain alkyl group, so that the phosphorus-containing polyarylether has a very good toughening effect, so that the epoxy resin adhesive has very good toughness and higher impact strength and bending strength while maintaining good mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, in particular to a preparation process of a flame retardant adhesive for copper clad laminates. Background Art

[0002] Copper clad laminates are mainly composed of insulating base film, conductive copper foil, resin adhesives, etc., and are widely used in PCB boards, computers, automotive electronic instruments, communication equipment, etc. Adhesives have a great influence on the flame retardancy, heat resistance, toughness and other properties of copper clad laminates, mainly epoxy resin adhesives, acrylate adhesives, etc. Among them, epoxy resin adhesives have good curing performance, high heat resistance, high strength, and are widely used. However, epoxy resin adhesives have problems such as poor toughness and poor flame retardancy, which are not conducive to their practical application in copper clad laminates and other aspects.

[0003] 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO and its derivatives are excellent phosphorus-based flame retardants, which can be made into nitrogen-phosphorus-based flame retardants, expansion flame retardants, macromolecular polymer flame retardants, etc., and are widely used in polymer materials such as epoxy resins, polyurethanes, and polypropylenes. Chinese patent CN101880395B discloses a polymer-type phosphorus-containing flame retardant containing DOPO and a preparation method thereof, wherein an aromatic diol modified with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is reacted with a dichlorinated substituted phosphate to obtain a polymer-type phosphorus-containing flame retardant, which improves the flame retardancy of epoxy resins and overcomes the shortcomings of small molecule phosphorus-based flame retardants such as poor compatibility with polymer matrices and easy migration. However, the polymer-type phosphorus-containing flame retardant does not improve the toughness and other properties of epoxy resins. Summary of the invention

[0004] The invention solves the problem that the epoxy resin adhesive for copper clad laminate has poor flame retardancy and toughness.

[0005] The technical solution of the present invention: The preparation process of the flame retardant adhesive for copper clad laminates comprises the following steps: Step A: Add N-methylpyrrolidone, toluene, 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, difluorophenylimide monomer, and potassium carbonate into a reaction vessel to perform azeotropic dehydration and polycondensation reaction. After cooling, pour the solution into an ethanol aqueous solution to precipitate a precipitate, filter it, wash it with water and ethanol, and dry it to obtain a phosphorus-containing polyarylether. The reaction formula is as follows:

[0006] Step B: adding a solvent, 100 parts by weight of epoxy resin, a cosolvent, and 10-25 parts by weight of phosphorus-containing polyarylether into a container, stirring, and then adding 0.4-0.7 parts by weight of a defoamer and 35-44 parts by weight of a curing agent to obtain a flame retardant adhesive for copper clad laminates.

[0007] Furthermore, in step A, the temperature of azeotropic dehydration is 150-160°C, and the time is 1-2h; the temperature of polycondensation reaction is 180-190°C, and the time is 8-12h.

[0008] Furthermore, in step A, the molar ratio of 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide (CAS registration number is 99208-50-1), difluorophenylimide monomer, and potassium carbonate is 1:(1-1.05):(1.5-1.7).

[0009] Furthermore, the solvent includes butanone, n-butanol, and butyl acetate, and the co-solvent includes N,N-dimethylformamide.

[0010] Furthermore, the curing agent includes 4,4-diaminodiphenyl sulfone and 4,4-diaminodiphenylmethane.

[0011] Further, the preparation process of difluorophenylimide monomer is: (1) Add glacial acetic acid, 3,5-diaminobenzoic acid and 4-fluorophthalic anhydride (CAS registration number: 319-03-9) in a molar ratio of (2-2.4):1 into a reaction vessel, heat to 115-125°C, condense and reflux to react for 10-15 hours, and after cooling, pour the solution into water to precipitate a precipitate. After filtering, the product is recrystallized in isopropanol to obtain a precursor.

[0012] (2) Add toluene, precursor, alkyl alcohol and p-toluenesulfonic acid in a molar ratio of 1: (2.6-3.2): (0.05-0.07) into a reaction vessel, heat to 100-110°C, condense and reflux for 6-8 hours, remove toluene by rotary evaporation, wash with petroleum ether, and recrystallize the product in isopropanol to obtain a difluorophenylimide monomer. The reaction formula is as follows:

[0013] Preferably, the molecular formula of the alkyl alcohol in (2) is OH-C n H 2n+1 , n is any integer from 8 to 14.

[0014] The technical effect of the present invention is as follows: 3,5-diaminobenzoic acid, 4-fluorophthalic anhydride and alkyl alcohol are used as reactants to prepare a novel difluorophenylimide monomer, which is then subjected to an etherification polycondensation reaction with 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide to obtain a phosphorus-containing polyarylether, which is finally mixed with an epoxy resin, a curing agent and the like to obtain a flame-retardant adhesive for copper-clad laminates. The main molecular chain of the phosphorus-containing polyarylether contains a DOPO group and a phenylimide ring structure to form a nitrogen-phosphorus flame-retardant system, which has a good condensed phase flame-retardant effect, forms an expanded carbon layer in the adhesive matrix during combustion, has an excellent flame-retardant effect, and significantly reduces the peak heat release rate and the total heat release.

[0015] The phosphorus-containing polyarylether of the invention contains a phenylimide ring with high rigidity and high structural stability, and the side chain contains a flexible long-chain alkyl group, which has a good toughening effect, so that the epoxy resin adhesive can maintain good mechanical strength while also showing good toughness, and has higher impact strength and bending strength. DETAILED DESCRIPTION

[0016] The technical solution of the present invention is further described below, but the scope of protection claimed is not limited to the description.

[0017] The epoxy resin model of the present invention is E51, and the defoaming agent brand is AGITAN A201. Example 1

[0018] (1) Add 120 mL of glacial acetic acid, 86 mmol of 3,5-diaminobenzoic acid, and 40 mmol of 4-fluorophthalic anhydride into a reaction vessel, heat to 115°C, and reflux under condensation for 15 h. After cooling, pour the solution into water to precipitate a precipitate. After filtering, the product is recrystallized in isopropanol to obtain a precursor.

[0019] (2) Add 30 mL of toluene, 30 mmol of the precursor, 78 mmol of 1-decanol, and 1.9 mmol of p-toluenesulfonic acid into a reaction container, heat to 110° C., condense and reflux for 6 h, remove toluene by rotary evaporation, wash with petroleum ether, and recrystallize the product in isopropanol to obtain a difluorophenylimide monomer.

[0020] (3) Add 150 mL of N-methylpyrrolidone, 100 mL of toluene, 40 mmol of 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, 40 mmol of difluorophenylimide monomer, and 60 mmol of potassium carbonate into a reaction container, heat to 150° C., remove water by azeotropic method for 2 h, then heat to 190° C., carry out polycondensation reaction for 8 h, cool the solution, pour it into an ethanol aqueous solution, precipitate, filter, wash with water and ethanol, and dry to obtain a phosphorus-containing polyarylether.

[0021] (4) 80 mL of butyl acetate, 100 g of epoxy resin, 10 mL of co-solvent N,N-dimethylformamide, and 10 g of phosphorus-containing polyarylether were added to a container, and after stirring, 0.4 g of a defoaming agent and 44 g of a curing agent 4,4-diaminodiphenyl sulfone were added to obtain a flame retardant adhesive for copper clad laminates. Example 2

[0022] (1) Add 100 mL of glacial acetic acid, 80 mmol of 3,5-diaminobenzoic acid, and 40 mmol of 4-fluorophthalic anhydride into a reaction vessel, heat to 125°C, and condense and reflux for 10 h. After cooling, pour the solution into water to precipitate a precipitate. After filtering, the product is recrystallized in isopropanol to obtain a precursor.

[0023] (2) Add 40 mL of toluene, 30 mmol of the precursor, 96 mmol of tetradecanol, and 1.5 mmol of p-toluenesulfonic acid into a reaction container, heat to 110° C., condense and reflux for 6 h, remove toluene by rotary evaporation, wash with petroleum ether, and recrystallize the product in isopropanol to obtain a difluorophenylimide monomer.

[0024] (3) Add 150 mL of N-methylpyrrolidone, 120 mL of toluene, 40 mmol of 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, 42 mmol of difluorophenylimide monomer, and 68 mmol of potassium carbonate into a reaction container, heat to 160° C., remove water by azeotropic means for 1 hour, then heat to 190° C., and perform polycondensation reaction for 8 hours. After cooling, pour the solution into an ethanol aqueous solution to precipitate a precipitate, filter, wash with water and ethanol, and dry to obtain a phosphorus-containing polyarylether.

[0025] (4) Add 80 mL of butanone, 100 g of epoxy resin, 20 mL of co-solvent N,N-dimethylformamide, and 17 g of phosphorus-containing polyarylether into a container, stir, add 0.7 g of defoaming agent, and 35 g of curing agent 4,4-diaminodiphenylmethane to obtain a flame retardant adhesive for copper clad laminates. Example 3

[0026] (1) Add 130 mL of glacial acetic acid, 96 mmol of 3,5-diaminobenzoic acid, and 40 mmol of 4-fluorophthalic anhydride into a reaction vessel, heat to 120°C, and condense and reflux for 10 h. After cooling, pour the solution into water to precipitate a precipitate. After filtering, the product is recrystallized in isopropanol to obtain a precursor.

[0027] (2) Add 40 mL of toluene, 30 mmol of the precursor, 84 mmol of 1-octanol, and 2.1 mmol of p-toluenesulfonic acid into a reaction container, heat to 100° C., condense and reflux for 8 h, remove toluene by rotary evaporation, wash with petroleum ether, and recrystallize the product in isopropanol to obtain a difluorophenylimide monomer.

[0028] (3) Add 150 mL of N-methylpyrrolidone, 120 mL of toluene, 40 mmol of 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, 40 mmol of difluorophenylimide monomer, and 68 mmol of potassium carbonate into a reaction container, heat to 150° C., remove water by azeotropic reaction for 2 h, then heat to 180° C., and perform polycondensation reaction for 12 h. After cooling, pour the solution into an ethanol aqueous solution to precipitate a precipitate, filter, wash with water and ethanol, and dry to obtain a phosphorus-containing polyarylether.

[0029] (4) Add 80 mL of n-butanol, 100 g of epoxy resin, 30 mL of co-solvent N,N-dimethylformamide, and 25 g of phosphorus-containing polyarylether into a container, stir, and then add 0.7 g of defoaming agent and 37 g of curing agent 4,4-diaminodiphenylmethane to obtain a flame retardant adhesive for copper clad laminates.

[0030] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no phosphorus-containing polyarylether is added.

[0031] (1) 80 mL of butyl acetate, 100 g of epoxy resin, and 10 mL of co-solvent N,N-dimethylformamide were added to a container, and after stirring, 0.4 g of a defoaming agent and 44 g of a curing agent 4,4-diaminodiphenyl sulfone were added to obtain an adhesive for copper clad laminates.

[0032] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that hydroquinone is used instead of 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide when preparing the polyarylether.

[0033] (1) Add 150 mL of N-methylpyrrolidone, 100 mL of toluene, 40 mmol of hydroquinone, 40 mmol of difluorophenylimide monomer, and 60 mmol of potassium carbonate into a reaction container, heat to 150°C, remove water by azeotropic method for 2 h, then heat to 190°C, carry out polycondensation reaction for 8 h, and after cooling, pour the solution into an ethanol aqueous solution to precipitate a precipitate, filter, wash with water and ethanol, and dry to obtain a polyarylether.

[0034] (2) 80 mL of butyl acetate, 100 g of epoxy resin, 10 mL of co-solvent N,N-dimethylformamide, and 10 g of polyarylether were added to a container, and after stirring, 0.4 g of a defoaming agent and 44 g of a curing agent 4,4-diaminodiphenyl sulfone were added to obtain an adhesive for copper clad laminates.

[0035] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that 4,4'-difluorobenzophenone is used instead of difluorophenylimide monomer when preparing the phosphorus-containing polyarylether.

[0036] (1) Add 150 mL of N-methylpyrrolidone, 100 mL of toluene, 40 mmol of 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, 40 mmol of 4,4'-difluorobenzophenone, and 60 mmol of potassium carbonate into a reaction container, heat to 150° C., remove water by azeotropic method for 2 h, then heat to 190° C., carry out polycondensation reaction for 8 h, cool the solution, pour it into an ethanol aqueous solution, precipitate, filter, wash with water and ethanol, and dry to obtain a phosphorus-containing polyarylether.

[0037] (2) 80 mL of butyl acetate, 100 g of epoxy resin, 10 mL of co-solvent N,N-dimethylformamide, and 10 g of phosphorus-containing polyarylether were added to a container, and after stirring, 0.4 g of a defoaming agent and 44 g of a curing agent 4,4-diaminodiphenyl sulfone were added to obtain a flame retardant adhesive for copper clad laminates.

[0038] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that ethanol is used instead of 1-decanol when preparing the difluorophenylimide monomer.

[0039] (1) Add 30 mL of toluene, 30 mmol of precursor, 78 mmol of ethanol, and 1.9 mmol of p-toluenesulfonic acid to a reaction vessel, heat to 110°C, condense and reflux for 6 hours, remove toluene by rotary evaporation, wash with petroleum ether, and recrystallize the product in isopropanol to obtain a difluorophenylimide monomer. The structural formula is:

[0040] (2) Add 150 mL of N-methylpyrrolidone, 100 mL of toluene, 40 mmol of 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, 40 mmol of difluorophenylimide monomer, and 60 mmol of potassium carbonate into a reaction container, heat to 150° C., remove water by azeotropic method for 2 h, then heat to 190° C., carry out polycondensation reaction for 8 h, cool the solution, pour it into an ethanol aqueous solution, precipitate, filter, wash with water and ethanol, and dry to obtain a phosphorus-containing polyarylether.

[0041] (3) 80 mL of butyl acetate, 100 g of epoxy resin, 10 mL of co-solvent N,N-dimethylformamide, and 10 g of phosphorus-containing polyarylether were added to a container, and after stirring, 0.4 g of a defoaming agent and 44 g of a curing agent 4,4-diaminodiphenyl sulfone were added to obtain a flame retardant adhesive for copper clad laminates.

[0042] The adhesive was coated on the surface of the polyimide film, and then the copper foil was attached to the surface of the polyimide film, pressed, and cured at 120°C for 1 hour and 150°C for 2 hours. The copper clad laminate specimen was made. The peel strength was tested using a tensile testing machine according to GB / T 7122-1996 standard, and the peeling speed was 50 mm / min.

[0043] Pour the adhesive into the mold, vacuum degassing, and cure it at 120°C for 2 hours and 150°C for 4 hours to make a casting sample. Test the impact strength and flexural strength according to GB / T 2567-2021.

[0044] The combustion properties of the cured adhesive samples were tested using a cone calorimeter. The thermal radiation flux was 35kW / m 2 .

[0045] Table 1

[0046] It can be seen from Table 1 that the epoxy resin adhesive of Comparative Example 1 has low impact strength and bending strength, poor toughness, large peak heat release rate and total heat release, and poor flame retardant performance.

[0047] Phosphorus-containing polyarylether is added to the epoxy resin adhesive of Examples 1-3, and its main molecular chain contains DOPO groups and phenylimide ring structures, forming a nitrogen-phosphorus flame retardant system, which plays a good condensed phase flame retardant role. When burning, an expanded carbon layer is formed in the adhesive matrix, which has an excellent flame retardant effect and significantly reduces the peak heat release rate and the total heat release. In addition, the phenylimide ring has high rigidity and high structural stability. At the same time, the side chain of the phosphorus-containing polyarylether contains flexible long-chain alkyl groups, which has a good toughening effect, so that the epoxy resin adhesive maintains good mechanical strength while also showing good toughness, and has higher impact strength and bending strength.

[0048] In Comparative Example 2, hydroquinone is used instead of 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide. The obtained polyarylether does not contain a DOPO structure and has a poor flame retardant effect on the epoxy resin adhesive, resulting in a large peak heat release rate and total heat release of the adhesive. However, the main chain of the polyarylether contains a rigid phenylimide ring and the side chain contains a flexible long-chain alkyl group, which has a good toughening effect and can improve the impact strength and bending strength of the adhesive.

[0049] Comparative Example 3 uses 4,4'-difluorobenzophenone instead of difluorophenylimide monomer, and the obtained phosphorus-containing polyarylether contains DOPO structure and has good flame retardant effect, but does not contain phenylimide ring structure, and does not form nitrogen-phosphorus flame retardant system, resulting in lower flame retardant effect than Example 1, and higher heat release rate peak and total heat release than Example 1. In addition, the side chain of the phosphorus-containing polyarylether does not contain flexible long-chain alkyl, and the toughening effect is poor, and the impact strength and flexural strength of the adhesive are low.

[0050] In Comparative Example 4, ethanol replaces 1-decanol, and the prepared difluorophenylimide monomer and phosphorus-containing polyarylether do not contain flexible long-chain alkyl groups, and the toughening effect is poor, and the impact strength and flexural strength of the adhesive are low.

[0051] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art of the present invention, several equivalent substitutions or obvious variations can be made without departing from the concept of the present invention, and the performance or use is the same, which should be regarded as belonging to the present invention.

Claims

1. A preparation process of a flame retardant adhesive for copper clad laminates, characterized in that: The preparation process comprises the following steps: Step A, adding N-methylpyrrolidone, toluene, 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, difluorophenylimide monomer, and potassium carbonate into a reaction container, performing azeotropic dehydration and polycondensation reaction, and after cooling, pouring the solution into an ethanol aqueous solution to precipitate a precipitate, filtering, washing with water and ethanol, and drying to obtain a phosphorus-containing polyarylether; The structural formula of the difluorophenylimide monomer is , n is any integer between 8 and 14; Step B: adding a solvent, 100 parts by weight of epoxy resin, a cosolvent, and 10-25 parts by weight of phosphorus-containing polyarylether into a container, stirring, and then adding 0.4-0.7 parts by weight of a defoamer and 35-44 parts by weight of a curing agent to obtain a flame retardant adhesive for copper clad laminates.

2. The preparation process of the flame retardant adhesive for copper clad laminate according to claim 1, characterized in that: In the step A, the temperature of azeotropic dehydration is 150-160° C., and the time is 1-2 hours; the temperature of polycondensation reaction is 180-190° C., and the time is 8-12 hours.

3. The preparation process of the flame retardant adhesive for copper clad laminate according to claim 1, characterized in that: In the step A, the molar ratio of 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, difluorophenylimide monomer and potassium carbonate is 1:(1-1.05):(1.5-1.7).

4. The preparation process of the flame retardant adhesive for copper clad laminate according to claim 3, characterized in that: The preparation process of the difluorophenylimide monomer is: (1) Add glacial acetic acid, 3,5-diaminobenzoic acid and 4-fluorophthalic anhydride to a reaction vessel, heat to 115-125°C, condense and reflux for 10-15 hours, and after cooling, pour the solution into water to precipitate a precipitate. After filtering, the product is recrystallized in isopropanol to obtain a precursor; (2) Add toluene, precursor, alkyl alcohol and p-toluenesulfonic acid into a reaction vessel, heat to 100-110° C., condense and reflux for 6-8 hours, remove toluene by rotary evaporation, wash with petroleum ether, and recrystallize the product in isopropanol to obtain a difluorophenylimide monomer.

5. The preparation process of the flame retardant adhesive for copper clad laminate according to claim 4, characterized in that: The molar ratio of 3,5-diaminobenzoic acid to 4-fluorophthalic anhydride in (1) is (2-2.4):

1.

6. The preparation process of the flame retardant adhesive for copper clad laminate according to claim 4, characterized in that: The molar ratio of the precursor, alkyl alcohol and p-toluenesulfonic acid in (2) is 1:(2.6-3.2):(0.05-0.07).

7. The preparation process of the flame retardant adhesive for copper clad laminate according to claim 6, characterized in that: The molecular formula of the alkyl alcohol in (2) is OH-C n H 2n+1 , n is any integer from 8 to 14.

8. The preparation process of the flame retardant adhesive for copper clad laminate according to claim 1, characterized in that: The solvent is butanone, n-butanol or butyl acetate, and the co-solvent is N,N-dimethylformamide.

9. The preparation process of the flame retardant adhesive for copper clad laminate according to claim 1, characterized in that: The curing agent includes 4,4-diaminodiphenyl sulfone and 4,4-diaminodiphenylmethane.

Citation Information

Patent Citations

  • Polymer type phosphorous flame retardant containing DOPO and preparation method thereof

    CN101880395B

  • Polyarylether with phosphaphenanthrene structure and method for synthesizing the same

    CN101565503A

  • High-toughness flame-retardant epoxy resin adhesive

    CN106833466A

  • Purification method of polyarylether and high-purity polyarylether

    CN115960354A

  • Preparation method of phosphaphenanthrene-structure reactive flame retardant and application thereof

    US20190382427A1